The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1021/bi00180a040
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of cytochrome P450 2B1 specificity: evidence for five substrate recognition sites

Abstract: Twelve site-directed mutants of rat cytochrome P450 2B1 distributed over seven positions and four putative substrate recognition sites (SRS) were constructed and expressed in COS cells. Function was examined using androstenedione and testosterone as substrates. Substitutions at positions 303, 360, and 473 did not markedly affect the regio- or stereoselectivity of androgen metabolism, whereas mutants in positions 206 (SRS-2), 302 (SRS-4), and 363 and 367 (SRS-5) exhibited markedly different steroid metabolite p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
73
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 35 publications
(58 reference statements)
9
73
0
Order By: Relevance
“…In fact, previous studies had already documented the functional significance of this variability. Mutagenesis of the position equivalent to amino acid 368 in several members of the CYP2B subfamily was shown to affect the regiospecific hydroxylation of steroids (52,53). The same position was also reported to play a role in substrate recognition for CYP2A5 (54) and CYP3A4 (55).…”
Section: -Epiaristolochene 13-dihydroxylasementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, previous studies had already documented the functional significance of this variability. Mutagenesis of the position equivalent to amino acid 368 in several members of the CYP2B subfamily was shown to affect the regiospecific hydroxylation of steroids (52,53). The same position was also reported to play a role in substrate recognition for CYP2A5 (54) and CYP3A4 (55).…”
Section: -Epiaristolochene 13-dihydroxylasementioning
confidence: 99%
“…SRS-5 and SRS-6 were of particular interest given their proximity to the active site in several P450 structures (51) and because specific amino acid positions within these regions have previously been correlated with regio-and stereospecific reaction mechanisms (Fig. 4A) (52)(53)(54)(55)(56)(57)(58)(59)(60)(61). A homology model of EAH derived from comparison with the mammalian CYP2C5 structure was constructed (Fig.…”
Section: -Epiaristolochene 13-dihydroxylasementioning
confidence: 99%
“…Halpert and coworkers have demonstrated that two other F helix residues, Phe-206 and Leu-209, determine the substrate specificity as well as the regioand stereoselectivity of P450 2B1 (He et al, 1994;Szklarz et al, 1995). Similar studies with Phe-209 in P450 2A5 have suggested that this F helix residue plays a critical role in determining substrate and product specificity and that the region around residue 209 constitutes the heme-substrate pocket in mammalian P450s (Lindberg and Negishi, 1989;Juvonen et al, 1991).…”
mentioning
confidence: 72%
“…Their studies have identified several residues required for 16␤-hydroxylation of testosterone and androstenedione. For example, mutations of Phe-115 to Ala, Phe-206 to Leu, Leu-209 to Ala, Ser-294 to Ala, Ala-298 to Val, Thr-302 to Ser, and Val-363 to Ala all diminished the 16␤-hydroxylation activity for androgens (He et al, 1994;Szklarz et al, 1995;). Together, , as well as the Thr-205 that has been identified in this study, contribute to the unique characteristics of P450 2B1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation